AKTYWNA POLITYKA ZATRUDNIENIA W AGLOMERACJI POZNAŃSKIEJ W LATACH 2002-2006 - Talaga, Robert (Wydział Prawa i Administracji UAM, 2008)
One of the crucial aspects of European regional policy is effective implementation of a labour market policy which constitutes a smooth employment increase. In order to develop effective methods of fighting unemployment, a whole spectrum of regulations setting out the objectives and relevant strategies and tools to achieve that goal have been presented. Each country develops its own measures and then uses them in practice, and it also creates regulations allowing them to operate effectively at both, national and regional, levels. The paper analyses the main objectives of the regional policy and tools that are used to achieve them, as well as key issues related to the labour market policy. The importance attached to the employment increase is confirmed by the vast range of aims and actions available to for successful implementation of an effective labour market policy. The regulations pinpoint the need of increasing employment through the human resources development, entrepreneurship support, education promotion and development o f employment institutions and labour market tools. The paper reports briefly on the active employment policy conducted in the poviat (county) of Poznań and city of Poznań, the so-called Poznań agglomeration and shows how the problem of unemployment in that region was combatted and solved in the years 2002-2006. The level of structural funds involved in the solving of that problem is then analysed. The study presented in the paper was intended to collect information and data to use them in comparative studies of regions of similar structures in Poland, in an attempt to collect more information on the actual Polands contribution in the implementation o f the European, national and regional labour market policy.
ACTIVE EMPLOYMENT POLICY IN POZNAŃ AGGLOMERATION IN THE PERIOD 2002-2006